2017
DOI: 10.1007/s00339-017-1392-5
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the stainless steel surface wettability by nanosecond direct laser texturing at high fluences

Abstract: This work investigates the influence of the direct laser texturing at high fluences (DLT-HF) on surface topography, chemistry and wettability. We use a Nd:YAG laser ( = 1064 nm) with pulse duration of 95 ns to process stainless steel surface. The surface morphology and chemistry after the texturing is examined by using scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), and electron backscatter diffraction (EBSD), while the surface wettability is evaluated by measuring the static c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 38 publications
7
76
0
Order By: Relevance
“…The processed surface was placed in a focal position. In this study, the laser-surface interaction leads to modification of both the surface chemistry and topography which, in fact, contribute to changes in the wettability of the surface [22].…”
Section: Design and Fabrication Of The Boiling Surfacesmentioning
confidence: 99%
“…The processed surface was placed in a focal position. In this study, the laser-surface interaction leads to modification of both the surface chemistry and topography which, in fact, contribute to changes in the wettability of the surface [22].…”
Section: Design and Fabrication Of The Boiling Surfacesmentioning
confidence: 99%
“…After DLT, all textured samples were superhydrophilic in a saturated Wenzel regime (a static contact angle equaled 0°), similar as in Ref. [5].…”
Section: Cylinder Surface Texturingmentioning
confidence: 72%
“…Their surfaces were modified by (DLT) with a nanosecond fiber laser. Several recent studies [3,4,5] have shown that DLT can be used for surface functionalization, since it influences on surface topography and also on surface wettability -immediately after DLT, the textured surfaces become superhydrophilic and after some time the transition to superhydrophobic state may occurs.…”
Section: Introductionmentioning
confidence: 99%
“…As the width of the microscopic features can be varied by the pulse/line spacing, the scan number has a greater effect on the feature height. In particular, nanosecond lasers have been used during the past for the fabrication of high aspect-ratio surface features, among others, demonstrated in [52,53]. A recent study reports on the gradually increase of the friction coefficient with higher line density [54].…”
Section: Deterministic Surface Textures and Groove Structuresmentioning
confidence: 99%
“…A recent study reports on the gradually increase of the friction coefficient with higher line density [54]. In any case, the fabrication of deterministic surface features with nanosecond lasers is characterized by strong material melting accompanied by a greater influence of the laser processing on the crystallographic structure, as observed up to 80 µm from the surface for the nanosecond laser regime [53]. This processing behavior can be a serious disadvantage that hinders the use of the cost-effective nanosecond laser technology for desired (micro-)engineering needs.…”
Section: Deterministic Surface Textures and Groove Structuresmentioning
confidence: 99%